The Impact of Late-Life Disability Spectrum on Depressive Symptoms: A Fixed-Effects Analysis of Panel Data. (1st May 2020) - Xiang, Xiaoling; Yang, Yong; Cheng, Jianjia; An, Ruopeng
Abstract: Objectives: This study examines the impact of a previously validated disability spectrum that accounts for compensatory strategies on depressive symptoms in older adults. Methods: This study was a secondary data analysis of 2011 through 2018 surveys from the National Health and Aging Trends Study ( N = 7, 609). The disability spectrum was categorized using a 5-level hierarchical scheme: fully able, successful accommodation, reduced activity, difficulty, and assistance for 12 mobility, self-care, and household activities. The individual fixed-effects panel model was used to examine the impact of this disability spectrum on depressive symptoms. Results: Depressive symptoms rose progressively with each successive category on the disability spectrum in descriptive analyses. In fixed-effects models, moving from "fully able" to "successful accommodation" was not associated with significant changes in depressive symptoms; this result held for all self-care and mobility activities. Moving from "fully able" to "reduced activity" was associated with a significant increase in depressive symptoms for 3 household activities (doing laundry, making hot meals, and shopping for groceries) but not for paying bills/banking or keeping track of medications. Going up 2 or more stages above "fully able" on the disability spectrum was associated with a significant increase in depressive symptoms across all 12 activities. Discussion: While limitations in a range of daily activities have harmful effects on mental health, using compensatory strategies that do not erode one's perception of autonomy can help older adults cope with the psychological detriments of late-life disability.